2020
DOI: 10.7150/jca.48939
|View full text |Cite
|
Sign up to set email alerts
|

High serum CCL20 is associated with tumor progression in penile cancer

Abstract: Serum cancer biomarker has been proven to be very valuable in cancer diagnosis, disease monitoring and prognosis assessment, despite there is still a lack of serum biomarker for penile cancer (PC). Our initial analysis on public GEO dataset identified CCL20 as a top C-C motif ligand (CCL) gene enriched in PC. The patients with PC exhibited markedly higher preoperative serum CCL20 level than healthy control. The area under the curve (AUC) was 0.855 with the sensitivity of 72.4%, and specificity of 93.5% to dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In addition, the key role of CCL20 in LUAD was identified in this study. CCL20, also called liver and activation-regulated chemokine, macrophage inflammatory protein 3 alpha, and small-inducible cytokine A20, is highly expressed in many types of cancer, including NSCLC, ovarian cancer, colorectal cancer, penile cancer, breast cancer, gastric cancer, and pancreatic cancer ( Han et al, 2015 ; Liu et al, 2016 ; Lee et al, 2017 ; Wang et al, 2019b ; Liu et al, 2020a ; Mo et al, 2020 ). This ligand has been found to enhance the migration and proliferation of cancer cells through the CCL20/CCR6 signaling pathway and to inhibit cell apoptosis, which directly promotes cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the key role of CCL20 in LUAD was identified in this study. CCL20, also called liver and activation-regulated chemokine, macrophage inflammatory protein 3 alpha, and small-inducible cytokine A20, is highly expressed in many types of cancer, including NSCLC, ovarian cancer, colorectal cancer, penile cancer, breast cancer, gastric cancer, and pancreatic cancer ( Han et al, 2015 ; Liu et al, 2016 ; Lee et al, 2017 ; Wang et al, 2019b ; Liu et al, 2020a ; Mo et al, 2020 ). This ligand has been found to enhance the migration and proliferation of cancer cells through the CCL20/CCR6 signaling pathway and to inhibit cell apoptosis, which directly promotes cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that RAB20 and IDO1 overexpression promote cell proliferation and induce immunosuppression in PSCC [ 11 , 21 ]. Other serum biomarkers, such as CXCL5, CXCL13, and CCL20, are associated with nodal metastasis in small cohorts [ 32 – 34 ]. The mechanisms underlying tumor metastasis are uncertain and have become an imminent issue.…”
Section: Discussionmentioning
confidence: 99%
“…Marchi et al utilized data from a public database identifying STAT1, which is potentially associated with dysfunction of the immune system, as prognostic factor for penile cancer (38). Later, it was found that the knockdown of CCL20, CXCL13, or CXCL5 gave the same results shown by significant suppression of STAT1 level and inhibition of MMP2 and MMP9 expression, leading to the diminished proliferation, migration, and invasion of penile cancer cells (39,40). SHCBP1 is a gene that has physiological associations with T cell proliferation and signaling.…”
Section: Discussionmentioning
confidence: 99%